Studies on some of mechanical properties of SS304L material under different heat treatment conditions - Hoang, Nhuan; Nguyen Thi, Thuc Phuong; Hoang, Xuan Thi; Tran, Xuan Vinh; Hoang, Thi Tuyen (Nuclear Science and Technology, 2017)
In the PWR pressure water reactor (PWR), stainless steel is used in many important parts in both primary and secondary water circuits. There are not enough necessary condition to experiment in extremly conditons of nuclear reactor, such as high temperature, high pressure in radiation environment in Vietnam. Therefore, in order to study the world’s technology for evaluating metal materials, it is necessary to have basic research on SS304 stainless steel objects. This study deals with SS304L stainless steel, which is low carbon steel used in nuclear power plants. The material used in this work was stainless steel 304 with low C content (SS304L). AISI stainless steel 304L plates were cut by wire-cutting machine into standard specimens and then heat-treated under different conditions. Finally, the post-treated specimens were tested by Rockwell hardness tester, tensile strength tester, and Charpy impact tester to verify the mechanical properties. The results showed that when heating the specimens in the range of 300÷900oC, cooling in the furnace to the room temperature, the value of hardness changed insignificantly. When increasing heating temperature, the yield strength and ultimate tensile strength values of the specimens decreased while the relative elongation values were almost unchanged. It means that under tested heat treatment conditions, the higher the heating temperature is, the worse mechanical properties are. The reason for this might be the appearance of the brittle sigma phase. Heat treatment results of SS304 specimens with the normalizing conditions at 900oC also shows the possibility to remove the sigma phase in the steel composition.